Vegetius : Epitome of military science - Vegetius, 383-450 (Translated texts for historians ;, 1996)
The only Latin art of war to survive, Vegetius’ Epitome was for long a part of the medieval prince’s military education. The core of his proposals, the maintenance of a professional standing army, was revolutionary for medieval Europe, while his theory of deterrence through strength remains the foundation of modern Western defence policy.